Immediate loading of four interforaminal implants supporting a locator‐retained mandibular overdenture in the elderly. Results of a 3‐year randomized, controlled, prospective clinical study. (27th June 2017) - Acham, Stephan; Rugani, Petra; Truschnegg, Astrid; Wildburger, Angelika; Wegscheider, Walther A.; Jakse, Norbert
Abstract: Background: Implant‐retained overdentures have become a standard option for the prosthetic treatment of the edentulous mandible in the elderly. Purpose: This prospective study aimed to compare immediate and conventional loading of four interforaminal implants supporting a Locator‐retained mandibular overdenture in elderly patients regarding implant survival, implant stability, and implant‐related complications. Material and methods: The study population comprised 20 completely edentulous patients (11 males) aged 60 years and older with severe mandible resorption. Each patient received four interforaminal implants (Neoss Ltd., Harrogate, UK). Following randomization, implants were loaded either immediately after dental implant surgery or 3 months after implant placement with the Locator‐abutment system. At follow‐up visits 3, 6 12, 24, and 36 months after loading, implant stability was evaluated with Periotest and Ostell. Results: Twenty patients received 80 implants. In eight patients, 32 implants were loaded immediately. Two patients had to be switched from the immediate to the conventional loading group due to insufficient primary stability (≤30 Ncm). Implant survival was similar in both groups after 36 months. No implant was lost. Decreasing Periotest, and accordingly, increasing Ostell measurements indicated adequate osseointegration in both groups. The course of treatment was not significantly different in the two groups. There were comparable incidences of postoperative complaints like swelling, hematoma, or wound dehiscence, as well as need for prosthetic treatment due to abutment loosening or occlusal discrepancies. Incidence of pressure marks and number of patient visits were significantly higher in the conventional loading group. Conclusion: With sufficient primary stability, immediate loading of four interforaminal implants in the edentulous mandible might be the preferential choice in the elderly, reducing total treatment time, and number of patient visits.